"Empreendedorismo" no contexto da uberização do trabalho no Brasil (2014 - 2020) - Akegawa, Rita de Cássia Dias (2021)
This dissertation addresses the work and training of the driver by application, specifically in the company Uber, in Brazil. Thus, the guiding question is to clarify the uberization and the effects of precarious work by the driver who uses the Uber application, under the methodology of historical-dialectical materialism. It is considered the thesis that the work of uberized drivers could offer an entrepreneurial means of being “the owner” of his own business, making use of his own efforts for his meritocratic performance; the antithesis resides in the phenomenon that the scaling up of Uber's business model is generated at the expense of workers who perform an alienated job of moving people with precarious work, without any rights; and the synthesis verified is based on the analysis of the contradictory that permeates the search for understanding uberization as a category, which brings technology closer to consumers in the service of an easier life, supporting capitalist companies at the expense of unassisted workers. In the context of the uberized work, it is important to argue and understand the new jobs that have been emerging in the shared economy scenario arising from the 4th Industrial Revolution. Therefore, it is essential to analyze and share the training for work, the labor activities that have been absorbing present workers and understand their future.